Beyond the HIPAA privacy rule enhancing privacy, improving health through research - Nass, Sharyl J.; Levit, Laura A.; Gostin, Lawrence O. (National Academies Press, 2009)
In the realm of health care, privacy protections are needed to preserve patients' dignity and prevent possible harms. Ten years ago, to address these concerns as well as set guidelines for ethical health research, Congress called for a set of federal stan.